Aplikasi Manajemen Kinerja Dalam Upaya Pengembangan Efektivitas Mutu Pelayanan Berbasis Teknologi Informasi - Fajri, Puspita Arta; Ikhwan, Khairul (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
BPN stands for National Land Agency in the form of a non-ministerial part of the government in Indonesia. BPN has duties in the Land sector. The work concept of the National Land Agency for the Sleman Regency branch holds full rules of fast work, hard work, and sincere work, in fact, it still intersects with a lack of services. BPN Kab. Sleman has problems with service quality. The purpose of this paper is to determine the importance and influence of the role of performance management and the development of information technology systems for the effectiveness of a service. The results, some researchers state that there is a big influence between performance management for the quality of service of a company with an information system that is also implemented.